Epidemiological Factors Associated with Dengue Shock Syndrome and Mortality in Hospitalized Dengue Patients in Ho Chi Minh City, Vietnam - Simmons, Cameron (2018)
Understanding trends in dengue disease burden and risk factors for severe disease can inform health service allocation, clinical management, and planning for vaccines and therapeutics. Dengue admissions at three tertiary hospitals in Ho Chi Minh City, Vietnam, increased between 1996 and 2009, peaking at 22,860 in 2008. Children aged 6-10 years had highest risk of dengue shock syndrome (DSS); however, mortality was highest in younger children and decreased with increasing age (odds ratio [OR] = 0.52, 95% confidence interval [CI] = 0.36-0.75 in 6- to 10- year-old children and OR = 0.27, 95% CI = 0.16-0.44 in 11- to 15-year-old children compared with 1- to 5-year-old children). Males were overrepresented among dengue cases; however, girls had higher risk of DSS (OR = 1.19, 95% CI = 1.14-1.24) and death (OR = 1.57, 95% CI = 1.14-2.17). Young children with dengue had greatest risk of death and should be targeted in dengue vaccine and drug trials. The increased risk of severe outcomes in girls warrants further attention in studies of pathogenesis, health-seeking behavior, and clinical care.